Job strain and cardiovascular risk factors: a cross sectional study of employed Danish men and women. Issue 10 (October 1991) - Netterstrøm, B; Kristensen, T S; Damsgaard, M T; Olsen, O; Sjøl, A
Abstract : As part of the World Health Organisation initiated MONICA project, 2000 men and women aged 30, 40, 50, and 60 from the general population were invited to undergo a medical examination with special emphasis on cardiovascular disease. A total of 1504 (75%) participated, 1209 of whom were employed. The participants answered a questionnaire on working, social, and health conditions and underwent clinical examinations that included the measurement of blood pressure and serum cholesterol, triglyceride, high density lipoprotein, fibrinogen, and glycated haemoglobin (HbA1C) concentrations. Using the demand-control model for measuring job strain suggested by Karasek, the employed people were classified according to those who had suffered job strain and those who had not in two different ways. The subjective classification was based on the participants' statements regarding demand and control in their jobs whereas the objective classification was based on job title and mode of payment. More women than men were classified as having high strain jobs. After adjusting for age and sex no significant association was found between coronary risk factors and subjective job strain. A tendency for an association between fibrinogen and job strain was found. Body mass index and HbA1C concentration were significantly associated with objective job strain independent of confounders.